PRINCIPLES AND PRACTICES OF REMOTE EDUCATION FOR LEARNERS IN CONDITIONS OF UNCERTAIN RISKS - Sharova , Tetiana; Artiomov , Mykola; Pastushenko , Sergij (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
This study addresses the urgent need to generalize the experience of implementing remote education in regions exposed to elevated risk levels. The research identifies effective practices and formulates actionable recommendations for educational institutions. These findings are relevant both for responding to emergency situations and for enhancing the resilience and adaptability of educational systems more broadly.